Efficacy of unilateral biportal endoscopy vs. unilateral portal endoscopy for the treatment of lumbar spinal stenosis: a systematic review and meta-analysis - Yu, Yongjia; An, Yuguang; Liu, Chang; Wang, Kemin; Liang, Wuqiao; Gan, Huazhong; Hong, Zhaoju; Zhang, Qingmei; He, Maolin; Feng, Daqin (Frontiers in Surgery, 2025)
BackgroundLumbar spinal stenosis (LSS) is a prevalent condition, particularly in aging populations, causing symptoms such as pain and disability. Unilateral Biportal Endoscopy (UBE) and Unilateral Portal Endoscopy (UPE) are minimally invasive techniques used to treat LSS. However, limited comparative data exist on their relative effectiveness. This systematic review and meta-analysis aimed to compare the clinical outcomes of UBE and UPE in treating LSS.MethodsA comprehensive search was performed in PubMed, Embase, Web of Science, and Cochrane Library on January 19, 2025, without time restrictions. Studies included in the analysis were cohort studies comparing UBE and UPE in patients with clinically diagnosed LSS. Key outcomes such as surgical duration, postoperative pain (VAS scores), functional disability (ODI), intraoperative blood loss, hospital stay, and complications were assessed. Data were analyzed using fixed- or random-effects models depending on heterogeneity.ResultsA total of six studies were included in the meta-analysis. No significant differences were observed between UBE and UPE in postoperative leg pain (VAS scores), back pain (VAS scores), or functional disability (ODI scores). The pooled data showed that both techniques provided comparable outcomes for pain relief and functional recovery. However, UBE was associated with significantly shorter surgical durations compared to UPE [SMD = −0.73, 95% CI (−1.39, −0.07)]. No significant differences were found in intraoperative blood loss, length of hospital stay, or postoperative complications between the two groups. Sensitivity analysis confirmed the robustness of the findings, and publication bias was not detected.ConclusionsBoth UBE and UPE are effective and comparable in treating LSS, with similar outcomes in terms of postoperative pain relief, functional recovery, and complications. UBE may offer the advantage of reduced surgical time. Further high-quality randomized controlled trials with longer follow-up are needed to validate these findings.Systematic Review Registrationidentifier (CRD420251090681).